A critical review of the capsaicin 8% patch for the treatment of neuropathic pain associated with diabetic peripheral neuropathy of the feet in adults. (4th March 2021) - Abrams, Rory M. C.; Pedowitz, Elizabeth J.; Simpson, David M.
ABSTRACT: Introduction: Diabetes is an increasingly prevalent disorder affecting nearly 1-in-5 adults, of which half will experience diabetic peripheral neuropathy (DPN) and a quarter will suffer from diabetic peripheral nerve pain (DPNP), severely impacting quality of life. The currently approved treatment options are typically centrally acting agents whose use is limited by systemic effects and drug interactions. The capsaicin 8% dermal patch was recently approved by the U.S. FDA for the treatment of DPNP. Areas covered: The authors review the available literature regarding the use of high-concentration capsaicin 8% patch for the treatment of diabetic peripheral neuropathy and neuropathic pain and discuss implementing its use in clinical practice. Expert opinion: The high-concentration capsaicin 8% patch is an effective and well-tolerated treatment option for treating DPNP. Capsaicin 8% patch may be used alone or in combination with other oral therapies and can provide rapid and sustained neuropathic pain relief following a single application and is safe and effective when used long term.